2018
DOI: 10.1111/ajad.12829
|View full text |Cite
|
Sign up to set email alerts
|

Drug use and hazardous drinking are associated with PTSD symptoms and symptom clusters in US Army Reserve/National Guard Soldiers

Abstract: Background and Objectives: There is strong evidence of the association between Posttraumatic Stress Disorder (PTSD) symptoms and substance use. Previous work has found sex differences in these associations. With revisions to the DSM, it is important to understand how overall PTSD symptoms and the new symptom clusters relate to substance use among Reserve/Guard soldiers-a high risk group. Methods: Data are from the baseline assessment of Operation: SAFETY (Soldiers and Families Excelling Through the Years), a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
(54 reference statements)
1
1
0
1
Order By: Relevance
“…The present analyses also suggest that these trauma exposure profiles are important for alcohol use outcomes even after accounting for PTSD, a known contributing factor to alcohol problems among military service members (Banducci et al., 2019; Homish et al., 2019; Walton et al., 2018). Specifically, the results indicate that R/NG soldiers with high levels of IPV exposure, in combination with slightly higher than average levels of combat exposure, are most consistently at risk for problematic alcohol use.…”
Section: Discussionsupporting
confidence: 51%
“…The present analyses also suggest that these trauma exposure profiles are important for alcohol use outcomes even after accounting for PTSD, a known contributing factor to alcohol problems among military service members (Banducci et al., 2019; Homish et al., 2019; Walton et al., 2018). Specifically, the results indicate that R/NG soldiers with high levels of IPV exposure, in combination with slightly higher than average levels of combat exposure, are most consistently at risk for problematic alcohol use.…”
Section: Discussionsupporting
confidence: 51%
“…Ergebnisse aus Langzeitstudien , die eine häufigere inzidente Substanzkonsumstörung nach Trauma und PTBS, nicht aber nach Trauma-Exposition alleine hervorhoben, gehen mit dieser Sichtweise ebenfalls gut konkordant [ 31 , 158 ]. Belege für eine Selbstmedikationshypothese erbrachten auch Detailstudien, die einen erhöhten Substanzkonsum in Abhängigkeit von definierten PTBS-Symptomclustern (Hyperarousal, Vermeidung, intrusive Wiedererinnerung; negative Trauma-assoziierte Stimmungen und Kognitionen) als Strategien einer Selbstregulation analysierten [ 29 , 57 , 62 , 80 , 124 , 172 , 201 ]. Generell stellte sich ein signifikanter Zusammenhang zwischen dem Gesamt-Score über alle PTBS-Symptomcluster und der Intensität des berichteten Cravings für die untersuchten Substanzen (Alkohol, Stimulantien, Opiate) dar.…”
Section: Trauma/ptbs Als Risikofaktor Für Substanzkonsumstörung – Sel...unclassified
“…Buckner and colleagues demonstrated that, among participants with PTSD who endorsed clinically significant hyperarousal symptoms, elevations in state anxiety predicted cannabis use (Buckner et al, 2018). PTSD may also be associated with an increased likelihood of using other psychoactive substances (Homish et al, 2019). Therefore, further research is needed to clarify whether PTSD symptom severity is associated specifically with high-risk alcohol use or generally with the use of other psychoactive substances.…”
mentioning
confidence: 99%